Eligibility to Use the Fund's Facilities for Concessional Financing, 2015. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
The review of PRGT eligibility continues to be guided by the principles of maintaining a transparent, rules-based, and parsimonious framework-ensuring uniformity of treatment across members in similar situations while taking appropriate account of country-specific circumstances. The graduation policy seeks to maintain broad alignment with the World Bank's IDA graduation practices, while also remaining consistent with the principle of ensuring the self-sustainability of the PRGT's lending capacity over time. The paper concludes that the existing framework remains broadly appropriate, but could be enhanced in a few areas, including: Making use of additional data sources, namely the IMF BEL database, in assessing that a country has durable and substantial market access, supplementing the current reliance on the World Bank's IDS database that is produced with a significant lag; Sharpening the specification of circumstances under which the presence of serious short-term vulnerabilities would justify non-graduation of a country that meets the income graduation criterion. This would entail limiting the application of the serious short-term vulnerabilities criterion for countries that exceed the applicable income graduation threshold by 50 percent or more.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet